2004
DOI: 10.4049/jimmunol.173.6.3979
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 3, a Class I Histone Deacetylase, Suppresses MAPK11-Mediated Activating Transcription Factor-2 Activation and Represses TNF Gene Expression

Abstract: During inflammatory events, the induction of immediate-early genes, such as TNF-α, is regulated by signaling cascades including the JAK/STAT, NF-κB, and the p38 MAPK pathways, which result in phosphorylation-dependent activation of transcription factors. We observed the direct interaction of histone deacetylase (HDAC) 3, a class I histone deacetylase, with MAPK11 (p38 β isoform) by West-Western-based screening analysis, pull-down assay, and two-hybrid system analysis. Results further indicated that HDAC3 decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 44 publications
1
54
2
1
Order By: Relevance
“…Both synthetic Vpr and TNF activate AP-1, JNK, NF-B (Figs. 1-3), and ATF-2 (data not shown), suggesting that they modulate the cellular machinery in a similar way and, therefore, could have the same effect on HIV replication in mononuclear phagocytes (71,80). We observed that synthetic Vpr, like TNF treatment, stimulates HIV-1 replication in the chronically infected promonocytic cell line U1 (70).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Both synthetic Vpr and TNF activate AP-1, JNK, NF-B (Figs. 1-3), and ATF-2 (data not shown), suggesting that they modulate the cellular machinery in a similar way and, therefore, could have the same effect on HIV replication in mononuclear phagocytes (71,80). We observed that synthetic Vpr, like TNF treatment, stimulates HIV-1 replication in the chronically infected promonocytic cell line U1 (70).…”
Section: Discussionmentioning
confidence: 70%
“…As a control, an anti-Vpr antibody was used (10 g/ml). activated protein kinase pathway, which is also involved in NF-B activation (54,67,71,74). Because typical HIV targets, such as monocytes or T cells, would be quiescent and unlikely to contain sufficient amounts of active transcription factor to support initial HIV replication (56), Vpr, in addition to transporting the preintegration virus RNA complex, also may serve to activate transcription factors such as AP-1 and NF-B and allow for an initial burst of HIV transcription (67).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested for the first time that HDAC3 is required for efficient gene expression via its role in activating signalling pathways. Previously HDAC3 has only been recognised for its role in suppressing signalling pathways such as p38, NF-κB and JAK/STAT (Chen et al, 2001;Mahlknecht et al, 2004;Togi et al, 2009). We over-expressed active and deacetylase-inactive forms of HDAC3 in our C3H10T1/2 cells but found no significant effect on the induction of a proximal promoter Timp-1 construct (Supp.…”
Section: Discussionmentioning
confidence: 99%